Method for preparing efficient and stable charcoal-based nano-catalyst based on Joule heating and regeneration method of efficient and stable charcoal-based nano-catalyst
The efficient and stable charcoal-based nanocatalyst prepared through Joule heating technology solves the problem of stable nucleation of metal nanocatalysts in the charcoal cell wall, achieves efficient catalytic activity and long-term stability, and realizes catalyst regeneration through multiple Joule heating treatments. It is suitable for clean energy production and water treatment fields.
Patent Information
- Application Number
- CN202411762014.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-03
AI Technical Summary
Existing metal nanocatalysts cannot stably nucleate in the charcoal cell wall, resulting in reduced catalytic activity and reaction efficiency, and it is difficult to have both efficient catalytic activity and long-term stability.
Joule heating technology is used to prepare efficient and stable charcoal-based nanocatalysts. Through transition metal salt solution drop coating, acid etching and Joule heating treatment, metal nanocatalysts are realized in the domain nucleation and surface interface regulation in the charcoal cell wall.
The efficient activity and long-term stability of charcoal-based nanocatalysts are achieved, and the efficient activity is shown in electrocatalytic water decomposition and analytical oxygen. The catalyst is "passivation-regeneration" through multiple Joule heating treatments, and the total number of cycles for degrading organic pollutants can reach 20 times.
Smart Images

Figure CN119565632A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a charcoal-based nano catalyst and a regeneration method thereof. Background Art
[0002] As a renewable resource with abundant reserves and environmental friendliness, wood is regarded as a natural "carbon reservoir" on Earth. Wood has an anisotropic hierarchical porous structure, good mechanical flexibility and tunable multifunctionality, which makes it widely used in many fields such as clean energy, catalytic engineering, environmental remediation, and intelligent manufacturing. Charcoal materials derived from natural wood can not only serve as carriers of functional nanomaterials, but also play a key role in reducing carbon emissions and prolonging carbon sequestration in the wood industry. In-depth exploration of the interface binding mechanism between charcoal cell walls and functional nanomaterials and their application in clean energy production and water treatment and purification are in line with the development needs of new quality productivity and are of great significance to the realization of low-carbon development and green economy.
[0003] The development of cost-effective, highly catalytically active and long-term stable carbon-based nanocatalysts is crucial to achieving clean energy production and environmental remediation. In recent years, a variety of interface engineering methods and surface modification strategies have been proposed, such as heteroatom doping, phase engineering, construction of heterogeneous interfaces, surface reconstruction, and induced lattice distortion. However, these methods are complex and costly, and ignore the interaction between nanocatalysts and conductive carbon substrates, and there is still room for improvement in manufacturing efficiency. Using low-cost and batch-preparable charcoal as a carrier, the low-temperature hydrothermal co-solvent method can achieve high mass loading of metal nanocatalysts on the cell wall. However, due to the slow heating rate, spatial limitations of the cell wall, and migration and agglomeration of metal nanoparticles, the active sites in the charcoal cell wall are unevenly distributed, and even active materials may fall off, resulting in reduced catalytic activity and reaction efficiency. In addition, other common nanomaterial preparation techniques, such as electrochemical deposition, air plasma treatment, microwave heating, chemical vapor deposition, and wet chemical methods, cannot solve the problem of stable nucleation of nanocatalysts on the charcoal cell wall. There are still certain challenges to achieve high-efficiency activity and long-term stability of catalysts simultaneously. Summary of the invention
[0004] The present invention aims to solve the problems that existing metal nanocatalysts cannot stably nucleate in charcoal cell walls and that charcoal-based nanocatalysts cannot have both efficient catalytic activity and stability, and further provide a method for preparing efficient and stable charcoal-based nanocatalysts based on Joule heating and a regeneration method thereof.
[0005] A method for preparing an efficient and stable charcoal-based nanocatalyst based on Joule heating is carried out in the following steps:
[0006] 1. Preparation of transition metal salt solution:
[0007] Adding a transition metal salt into a solvent and stirring to mix uniformly to obtain a transition metal salt solution;
[0008] The concentration of the transition metal salt solution is 0.05 mol / L to 0.25 mol / L;
[0009] 2. Carbonization activation:
[0010] The wood is subjected to carbonization treatment and activation treatment in sequence to obtain activated charcoal;
[0011] 3. Acid etching:
[0012] The activated charcoal is immersed in an acid solution, etched for 10 minutes to 30 minutes at a temperature of 15° C. to 35° C., and then ultrasonically cleaned to obtain acid-treated charcoal;
[0013] 4. Surface coating:
[0014] ① Apply the transition metal salt solution to the surface of the acid-treated charcoal to fully wet the surface, and then vacuum-treat the wetted charcoal;
[0015] ② Repeat step 4① 3 to 5 times to obtain charcoal after drop coating and impregnation, and heat the charcoal after drop coating and impregnation at a temperature of 50°C to 90°C for 8h to 24h to obtain charcoal loaded with a metal salt precursor;
[0016] 5. Joule heating treatment:
[0017] ① Fix the charcoal loaded with the metal salt precursor on the copper electrode of the Joule heating device, perform carbon thermal shock treatment for 0.5s to 2.5s at a temperature of 700℃ to 2400℃ and an argon gas rate of 0.2L / min to 0.8L / min, and finally cool to room temperature;
[0018] ② Repeat step 5① 1 to 3 times to obtain a highly efficient and stable charcoal-based nanocatalyst.
[0019] The regeneration method of the highly efficient and stable charcoal-based nanocatalyst is carried out according to the following steps:
[0020] ① The passivated efficient and stable charcoal-based nanocatalyst is fixed on the copper electrode of the Joule heating device, and the temperature is increased to 700°C to 2400°C at a heating rate of 8000°C / s to 12000°C / s, and carbon thermal shock treatment is performed for 0.5s to 2.5s at a temperature of 700°C to 2400°C and an argon gas rate of 0.2L / min to 0.8L / min, and finally cooled to room temperature at a cooling rate of 2000°C / s to 2500°C / s;
[0021] ② Repeat step ① 1 to 3 times to complete the regeneration method.
[0022] The beneficial effects of the present invention are:
[0023] The present invention uses the good adsorption effect between charcoal defects and liquid metal, integrates Joule heating and rapid cooling technology, allows the metal nanocatalyst to be confined in the cell wall of charcoal, and simultaneously realizes the surface and interface regulation of charcoal-based nanocatalysts. Compared with traditional heating modes (such as tubular furnace heating), electrochemical deposition, air plasma treatment, wet chemical reduction and vapor deposition strategies, Joule heating technology has the advantages of rapid synthesis (0.5s to 2.5s), small particle size (particle size range is 10nm to 38nm), uniform dispersion and embedded structure. The prepared charcoal-based nanocatalyst not only has high activity in electrocatalytic water decomposition of oxygen (at 10mA cm -2 The oxygen evolution overpotential at the current density is 178mV; at 100mAcm -2 The oxygen evolution overpotential at the current density is 320 mV, and it exhibits long-term stability (at 100 mA cm -2 at the same time, multiple Joule heating treatments can realize the "passivation-regeneration" of charcoal-based single metal atom catalysts (that is, after multiple cycle experiments, the surface of charcoal-based nanocatalysts is covered with a large number of degradation intermediates, thereby reducing the utilization rate of active metal sites; after multiple high-temperature thermal shock treatments, the reaction intermediates can be thermally degraded into graphite carbon layers, which not only promotes the recovery of active metal sites, but also enhances the local electron transfer of the catalyst, thereby realizing the regeneration of the nanocatalyst). The total number of cycles for degrading organic pollutants can reach 20 times (the total number of cycles includes the initial number of cycles plus the number of cycles after regeneration, and the degradation efficiency is maintained at more than 90%). The prepared charcoal-based nanocatalysts have a wide range of applications in clean energy production, water treatment and other fields.
[0024] Instruction Manual
[0025] Figure 1 This is a macroscopic photograph of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1;
[0026] Figure 2 The temperature-time curve of Joule heating and rapid quenching treatment in step 5① of Example 1;
[0027] Figure 3 This is a physical diagram of the Joule heating process in step 5① of embodiment 1;
[0028] Figure 4 This is a scanning electron microscope image of a longitudinal section of the activated charcoal prepared in step 2 of Example 1, magnified 200 times;
[0029] Figure 5 This is a diagram of the specific surface area of the activated charcoal prepared in step 2 of Example 1;
[0030] Figure 6 This is a scanning electron microscope image of a longitudinal section of the acid-treated charcoal prepared in step 3 of Example 1, magnified 100,000 times;
[0031] Figure 7 The scanning electron microscope images of the cross section and the longitudinal section of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1 are magnified 100 times;
[0032] Figure 8 This is a scanning electron microscope image of a longitudinal section of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1, magnified 20,000 times;
[0033] Fig. 9 This is a scanning electron microscope image of a longitudinal section of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1, magnified 60,000 times;
[0034] Fig.10 This is a transmission electron microscopy image of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1;
[0035] Fig.11 This is a particle size distribution diagram of the nanocatalyst in the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1;
[0036] Fig.12 1 is an X-ray diffraction spectrum, 1 is a highly efficient and stable charcoal-based nanocatalyst prepared in Example 1, 2 is the activated charcoal prepared in step 2 of Example 1;
[0037] Fig.13 The polarization curves of the oxygen evolution reaction (OER) of the highly efficient and stable charcoal-based nanocatalysts prepared in Examples 1 to 3 are shown in Figure 1, 2 is Example 1, and 3 is Example 3;
[0038] Fig.14 The high efficiency and stable charcoal-based nanocatalyst prepared in Example 1 was 100 mA cm -2 Stability curve under current density;
[0039] Fig.15 The degradation efficiency of Rhodamine B by the highly efficient and stable charcoal-based nanocatalysts prepared by different heating processes is shown in Figure 1, which is Example 4, 2 is Example 5, and 3 is Example 6;
[0040] Fig.16 This is a scanning electron microscopic image of the longitudinal section of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 4 after passivation during the degradation of Rhodamine B;
[0041] Fig.17This is a scanning electron microscope image of a longitudinal section of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 4 after passivation and regeneration by Joule heating treatment;
[0042] Fig.18 This is a transmission electron microscope image of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 4 after passivation and regeneration by Joule heating treatment;
[0043] Fig.19 This is a graph showing the degradation efficiency of Rhodamine B during 20 cycles of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 4. DETAILED DESCRIPTION
[0044] Specific implementation method 1: This implementation method is a method for preparing efficient and stable charcoal-based nanocatalysts based on Joule heating, which is carried out in the following steps:
[0045] 1. Preparation of transition metal salt solution:
[0046] Adding a transition metal salt into a solvent and stirring to mix uniformly to obtain a transition metal salt solution;
[0047] The concentration of the transition metal salt solution is 0.05 mol / L to 0.25 mol / L;
[0048] 2. Carbonization activation:
[0049] The wood is subjected to carbonization treatment and activation treatment in sequence to obtain activated charcoal;
[0050] 3. Acid etching:
[0051] The activated charcoal is immersed in an acid solution, etched for 10 minutes to 30 minutes at a temperature of 15° C. to 35° C., and then ultrasonically cleaned to obtain acid-treated charcoal;
[0052] 4. Surface coating:
[0053] ① Apply the transition metal salt solution to the surface of the acid-treated charcoal to fully wet the surface, and then vacuum-treat the wetted charcoal;
[0054] ② Repeat step 4① 3 to 5 times to obtain charcoal after drop coating and impregnation, and heat the charcoal after drop coating and impregnation at a temperature of 50°C to 90°C for 8h to 24h to obtain charcoal loaded with a metal salt precursor;
[0055] 5. Joule heating treatment:
[0056] ① Fix the charcoal loaded with the metal salt precursor on the copper electrode of the Joule heating device, perform carbon thermal shock treatment for 0.5s to 2.5s at a temperature of 700℃ to 2400℃ and an argon gas rate of 0.2L / min to 0.8L / min, and finally cool to room temperature;
[0057] ② Repeat step 5① 1 to 3 times to obtain a highly efficient and stable charcoal-based nanocatalyst.
[0058] In step 2, the pretreated wood is carbonized in a vacuum tube furnace, and the overall morphology and structure of the wood cell wall can be completely preserved and completely converted into the main structure of the charcoal material; then it is continued to be heated in a CO2 atmosphere to obtain activated charcoal.
[0059] The purpose of step two is mainly to convert natural wood into charcoal by pyrolysis and carbonization, which not only gives the wood good electrical conductivity, but also maintains a hierarchical porous structure; at the same time, the charcoal after CO2 activation treatment has a certain degree of defect.
[0060] Principle of step two: During the low-temperature carbonization process, the structure of the cell wall and cell cavity will change significantly. The wood components such as cellulose, hemicellulose, and lignin in the cell wall form a graphite structure in the amorphous carbon through dehydration, decarboxylation, and intramolecular condensation. The carbon layer presents a vortex-like, disordered microstructure, and there are defects, nanopores, and voids on the surface. At the same time, CO2 can be confined in a layered porous structure, and by reacting with impurities such as amorphous carbon in the wood, it etches the carbon atoms in the wood cell wall to open pores with smaller pores, and then forms new micropores under continuous activation; the removal of carbon atoms is conducive to the disordering of the structure and surface reconstruction, resulting in certain defective structures in the treated wood.
[0061] In step three, the activated charcoal is immersed in an acid solution, etched, and then the pH of the solution is adjusted to neutral to obtain acid-treated wood.
[0062] The purpose of step three is to introduce an acid etching method to treat the activated charcoal and further introduce defect sites on the surface of the charcoal substrate.
[0063] Mechanism of step three: After the activated charcoal is immersed in an acid solution (such as nitric acid), an oxidation reaction can occur to generate products such as carbon dioxide, nitrogen oxides and water. This oxidation reaction can change the surface properties of the charcoal substrate, such as increasing the surface roughness, etching the surface of the carbon substrate, and even destroying its local structure, thereby further introducing defects in the charcoal substrate.
[0064] Principle of step 4: The hierarchical porous structure of charcoal facilitates the penetration of transition metal salt solution and fully impregnation into the charcoal cell wall; surface drip coating treatment can achieve uniform dispersion of metal salt precursors and avoid particle agglomeration during high temperature impact.
[0065] Principle of step 5①: In the cell wall of wood, defects drive the confined nucleation of metal nanocatalysts, which is due to the good adsorption of metal droplets at defect sites at high temperatures. However, after partial graphitization and carbon dioxide activation at lower temperatures, charcoal will have a certain degree of carbon defects. After Joule heating and rapid quenching treatment, it can not only induce continuous fission of metal particles to form small-sized and well-dispersed nanoparticles, but also promote the carbon atoms adjacent to the metal nanocatalyst to derive a crystalline graphite structure through continuous high-temperature shock, thereby realizing the self-encapsulation of high-entropy alloy nanoparticles in the charcoal cell wall and forming an efficient and stable charcoal-based nanocatalyst.
[0066] Regeneration principle of charcoal catalyst: During the cyclic degradation test, the decrease in degradation efficiency is mainly attributed to the accumulation of degradation intermediates on the catalyst surface and the depletion of active metal sites. The reaction intermediates loaded on the passivated charcoal-based nanocatalyst can be pyrolyzed into a carbon layer after multiple Joule heating high-temperature shocks. The newly formed carbon layer promotes the interfacial electron transfer between the metal site and the reaction system, thereby achieving high efficiency and secondary activation regeneration of the charcoal-based nanocatalyst.
[0067] The beneficial effects of this embodiment are:
[0068] This embodiment uses the good adsorption effect between charcoal defects and liquid metal, integrates Joule heating and rapid cooling technology, allows the metal nanocatalyst to be confined in the cell wall of charcoal, and simultaneously realizes the surface and interface regulation of charcoal-based nanocatalysts. Compared with traditional heating modes (such as tubular furnace heating), electrochemical deposition, air plasma treatment, wet chemical reduction, and vapor deposition strategies, Joule heating technology has the advantages of rapid synthesis (0.5s to 2.5s), small particle size (particle size range is 10nm to 38nm), uniform dispersion, and embedded structure. The prepared charcoal-based nanocatalyst is not only highly active in electrocatalytic water decomposition and oxygen (at 10mA cm -2 The oxygen evolution overpotential at the current density is 178mV; at 100mAcm -2 The oxygen evolution overpotential at the current density is 320mV, and it shows long-term stability (at 100mAcm -2at the same time, multiple Joule heating treatments can realize the "passivation-regeneration" of charcoal-based single metal atom catalysts (that is, after multiple cycle experiments, the surface of charcoal-based nanocatalysts is covered with a large number of degradation intermediates, thereby reducing the utilization rate of active metal sites; after multiple high-temperature thermal shock treatments, the reaction intermediates can be thermally degraded into graphite carbon layers, which not only promotes the recovery of active metal sites, but also enhances the local electron transfer of the catalyst, thereby realizing the regeneration of the nanocatalyst). The total number of cycles for degrading organic pollutants can reach 20 times (the total number of cycles includes the initial number of cycles plus the number of cycles after regeneration, and the degradation efficiency is maintained at more than 90%). The prepared charcoal-based nanocatalysts have a wide range of applications in clean energy production, water treatment and other fields.
[0069] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the transition metal salt described in step 1 is one of iron salt, cobalt salt, nickel salt, chromium salt and manganese salt or a combination of several thereof; the solvent described in step 1 is distilled water or anhydrous ethanol; the stirring and mixing described in step 1 is specifically stirring for 12h to 36h under the condition of a rotation speed of 300rpm to 600rpm. The rest is the same as specific implementation method 1.
[0070] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the iron salt is iron nitrate, iron chloride or iron acetate; the cobalt salt is cobalt nitrate, cobalt chloride or cobalt acetate; the nickel salt is nickel nitrate, nickel chloride or nickel acetate; the chromium salt is chromium nitrate, chromium chloride or chromium acetate; the manganese salt is manganese nitrate, manganese chloride or manganese acetate. The rest is the same as specific implementation method one or two.
[0071] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that: the wood described in step 2 is pretreated wood, and the pretreatment is specifically carried out according to the following steps: soaking the wood in distilled water or ethanol solution, ultrasonic cleaning for 1h to 3h at a power of 100W to 300W, and then vacuum drying for 1h to 24h at a temperature of 40℃ to 80℃ to obtain the pretreated wood. The rest is the same as specific embodiments 1 to 3.
[0072] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that the thickness of the wood in step 2 is 0.5 mm to 2.5 mm; the wood in step 2 is coniferous wood or broadleaf wood, and the cutting method is transverse cutting or tangential cutting. The rest is the same as specific implementation methods 1 to 4.
[0073] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: in step 2, the wood is sequentially carbonized and activated, specifically according to the following steps: the wood is carbonized for 4h to 8h at a temperature of 800°C to 1200°C and a nitrogen flow rate of 0.2L / min to 0.6L / min, and after cooling to room temperature, the carbonized wood is obtained, and then the carbonized wood is activated for 2h to 10h at a temperature of 660°C to 860°C and a carbon dioxide flow rate of 0.05L / min to 0.2L / min, and after cooling to room temperature, the activated charcoal is obtained. The rest is the same as specific embodiments 1 to 5.
[0074] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that: the concentration of the acid solution in step 3 is 5wt% to 25wt%; the acid solution in step 3 is a nitric acid solution or a hydrochloric acid solution; the ultrasonic cleaning in step 3 is specifically carried out according to the following steps: using distilled water or anhydrous ethanol as a washing liquid, ultrasonic cleaning is performed at a power of 200W to 500W until the pH of the solution is neutral. The rest is the same as specific embodiments 1 to 6.
[0075] Specific embodiment 8: This embodiment differs from any one of the specific embodiments 1 to 7 in that: in step 4①, the drop coating amount is 2 mL / cm 2 ~5mL / cm 2 , drip the transition metal salt solution onto the surface of the acid-treated charcoal to fully wet the surface, and then vacuum-treat the wetted charcoal for 24h to 72h in a vacuum environment at a temperature of 15°C to 25°C and a vacuum degree of 10Pa to 10kPa. The rest is the same as the first to seventh embodiments.
[0076] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that: in step 5①, the charcoal loaded with the metal salt precursor is fixed on the copper electrode of the Joule heating device, and the temperature is increased to 700℃~2400℃ at a heating rate of 8000℃ / s~12000℃ / s, and the carbon thermal shock treatment is performed for 0.5s~2.5s at a temperature of 700℃~2400℃ and an argon gas rate of 0.2L / min~0.8L / min, and finally cooled to room temperature at a cooling rate of 2000℃ / s~2500℃ / s. The rest is the same as specific embodiments 1 to 8.
[0077] Specific embodiment 10: The regeneration method of the charcoal-based nanocatalyst with high efficiency and stability in this embodiment is carried out according to the following steps:
[0078] ① The passivated efficient and stable charcoal-based nanocatalyst is fixed on the copper electrode of the Joule heating device, and the temperature is increased to 700°C to 2400°C at a heating rate of 8000°C / s to 12000°C / s, and carbon thermal shock treatment is performed for 0.5s to 2.5s at a temperature of 700°C to 2400°C and an argon gas rate of 0.2L / min to 0.8L / min, and finally cooled to room temperature at a cooling rate of 2000°C / s to 2500°C / s;
[0079] ② Repeat step ① 1 to 3 times to complete the regeneration method.
[0080] The following examples are used to verify the beneficial effects of the present invention:
[0081] Embodiment 1:
[0082] A method for preparing an efficient and stable charcoal-based nanocatalyst based on Joule heating is carried out in the following steps:
[0083] 1. Preparation of transition metal salt solution:
[0084] Under the condition of a rotation speed of 500 rpm, a transition metal salt is added into the solvent and stirred for 24 hours to obtain a transition metal salt solution;
[0085] The concentration of the transition metal salt in the transition metal salt solution is 0.05 mol / L; the transition metal salt is a combination of iron salt, cobalt salt, nickel salt, chromium salt and manganese salt in a molar ratio of 1:1:1:1:1; the solvent is anhydrous ethanol;
[0086] The iron salt is ferric chloride; the cobalt salt is cobalt chloride; the nickel salt is nickel chloride; the chromium salt is chromium chloride; the manganese salt is manganese chloride;
[0087] 2. Carbonization activation:
[0088] The wood was carbonized at 1000°C and a nitrogen flow rate of 0.2 L / min for 6 h, and then cooled to room temperature to obtain carbonized wood. The carbonized wood was then activated at 760°C and a carbon dioxide flow rate of 0.05 L / min for 6 h, and then cooled to room temperature to obtain activated charcoal.
[0089] The wood is pretreated wood, and the pretreatment is specifically carried out according to the following steps: soaking the wood in distilled water, ultrasonically cleaning it for 2 hours at a power of 200 W, and then vacuum drying it for 12 hours at a temperature of 60° C. to obtain the pretreated wood;
[0090] The thickness of the wood is 2 mm; the wood is basswood, and the cutting method is horizontal cutting;
[0091] 3. Acid etching:
[0092] The activated charcoal was immersed in an acid solution, etched for 20 minutes at a temperature of 25°C, and then ultrasonically cleaned at a power of 400W using distilled water as a washing liquid until the pH of the solution was neutral, thereby obtaining acid-treated charcoal;
[0093] The concentration of the acid solution is 10wt%; the acid solution is a nitric acid solution;
[0094] 4. Surface coating:
[0095] ① The drop coating volume is 3mL / cm 2 , drop the transition metal salt solution onto the surface of the acid-treated charcoal to fully wet the surface, and then vacuum treat the wetted charcoal for 48 hours in a vacuum environment at a temperature of 25°C and a vacuum degree of 20Pa;
[0096] ② Repeat step 4① 3 times to obtain charcoal after drop coating and impregnation, and heat the charcoal after drop coating and impregnation at 80°C for 24 hours to obtain charcoal loaded with metal salt precursor;
[0097] 5. Joule heating treatment:
[0098] ① The charcoal loaded with metal salt precursor was fixed on the copper electrode of the Joule heating device, heated to 1800°C at a heating rate of 11000°C / s, and subjected to carbon thermal shock treatment for 2s at a temperature of 1800°C and an argon gas rate of 0.2L / min, and finally cooled to room temperature at a cooling rate of 2500°C / s;
[0099] ② Repeat step 5① once to obtain a highly efficient and stable charcoal-based nanocatalyst.
[0100] Example 2: This comparative experiment is different from Example 1 in that the transition metal salt described in step 1 is a combination of iron salt, cobalt salt, nickel salt and manganese salt in a molar ratio of 1:1:1:1. The rest is the same as Example 1.
[0101] Example 3: This comparative experiment is different from Example 1 in that the transition metal salts described in step 1 are iron salt, cobalt salt and nickel salt in a molar ratio of 1:1:1. The rest is the same as Example 1.
[0102] Example 4: This comparative experiment is different from Example 1 in that the transition metal salt in step 1 is a cobalt salt; in step 5, the temperature is raised to 700°C at a heating rate of 11000°C / s, and carbon thermal shock treatment is performed for 2s at a temperature of 700°C and an argon gas rate of 0.2L / min. The rest is the same as Example 1.
[0103] Example 5: This comparative experiment is different from Example 1 in that the transition metal salt in step 1 is a cobalt salt; in step 5, the temperature is raised to 1200°C at a heating rate of 11000°C / s, and carbon thermal shock treatment is performed for 2s at a temperature of 1200°C and an argon gas rate of 0.2L / min. The rest is the same as Example 1.
[0104] Example 6: This comparative experiment is different from Example 1 in that the transition metal salt in step 1 is a cobalt salt; in step 5, the temperature is raised to 1600°C at a heating rate of 11000°C / s, and carbon thermal shock treatment is performed for 2s at a temperature of 1600°C and an argon gas rate of 0.2L / min. The rest is the same as Example 1.
[0105] Figure 1 This is a macroscopic photograph of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1. As can be seen from the figure, the charcoal after carbonization activation and Joule heating treatment presents a rigid and complete structure.
[0106] Figure 2 The temperature-time curve of Joule heating and rapid quenching treatment in step 5① of Example 1. As can be seen from the figure, after applying a DC pulse, the charcoal surface loaded with a metal salt precursor is instantly heated to 1800°C within 0.16s; the metal salt precursor is converted into molten metal droplets within 2s, and the nanoparticles are evenly dispersed on the surface of the charcoal electrode after rapid cooling.
[0107] Figure 3 This is a physical diagram of the Joule heating process in step 5① of embodiment 1. As can be seen from the figure, the ultra-high temperature generated by Joule heating can achieve sufficient heating of the charcoal electrode.
[0108] Figure 4 This is a scanning electron microscope image of a longitudinal section of the activated charcoal prepared in step 2 of Example 1 at a magnification of 200 times. As can be seen from the image, the activated charcoal exhibits a hierarchical porous structure.
[0109] Figure 5 This is the specific surface area of the activated charcoal prepared in step 2 of Example 1. As can be seen from the figure, the specific surface area of the activated charcoal can reach 754m 2 g -1 , proving that more smaller pores were opened and new micropores were formed after activation.
[0110] Figure 6 This is a scanning electron microscope image of a longitudinal section of the acid-treated charcoal prepared in step 3 of Example 1, magnified 100,000 times. As can be seen from the image, the acid solution etches the surface of the carbon substrate and even destroys its local structure, thereby further introducing defects into the charcoal substrate.
[0111] Figure 7 The scanning electron microscope images of the cross section and longitudinal section of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1 are magnified 100 times. As can be seen from the figure, the charcoal-based nanocatalyst presents a multi-channel structure with low tortuosity, which helps to enhance mass transfer in the electrochemical energy conversion process.
[0112] Figure 8 This is a scanning electron microscope image of a longitudinal section of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1, magnified 20,000 times. As can be seen from the image, the high entropy alloy nanoparticles are densely and evenly dispersed throughout the wood channel.
[0113] Fig. 9 This is a 60,000-fold magnified longitudinal section scanning electron microscope image of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1. As can be seen from the figure, most of the high-entropy alloy nanoparticles are semicircular, indicating that the particles have been embedded in the charcoal cell wall, which enables them to accelerate the interfacial charge transfer between the charcoal substrate and the catalyst during the oxygen evolution reaction.
[0114] Fig.10 This is a transmission electron microscope image of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1; as can be seen from the figure, after Joule heating shock, a few layers of graphite carbon structure appear around the high entropy alloy nanoparticles, further strengthening the interfacial charge transfer between the charcoal substrate and the catalyst.
[0115] Fig.11 The particle size distribution diagram of the nanocatalyst in the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1. As can be seen from the figure, the particle size range of the high entropy alloy nanoparticles is 10nm to 38nm. Compared with the catalysts with particle sizes of several hundred nanometers prepared by traditional heating methods (such as tubular furnace pyrolysis), the charcoal-based nanocatalyst prepared by this Joule heating method significantly improves the utilization rate of active sites and increases the accessibility of active centers and electrolyte ions. This smaller particle size is mainly caused by the continuous fission of particles at carbon defects during the Joule heating process.
[0116] Fig.12 1 is an X-ray diffraction spectrum, 1 is the highly efficient and stable charcoal-based nanocatalyst prepared in Example 1, and 2 is the charcoal after activation treatment prepared in step 2 of Example 1. As can be seen from the figure, the high entropy alloy nanoparticles show a single-phase alloy structure.
[0117] Fig.13 The polarization curves of the oxygen evolution reaction (OER) of the highly efficient and stable charcoal-based nanocatalysts prepared in Examples 1 to 3 are shown in Figure 1 for Example 1, 2 for Example 2, and 3 for Example 3. As can be seen from the figure, the charcoal-based nanocatalyst prepared in Example 1 has a high conductivity at 10 mA cm -2 The oxygen evolution overpotential at the current density is 178mV, and at 100mAcm -2The oxygen evolution overpotential at this current density is 320 mV, and the complexity of its high-entropy configuration and synergistic effect help accelerate the OER kinetics.
[0118] Fig.14 The high-efficiency and stable charcoal-based nanocatalyst prepared in Example 1 has a conductivity of 100 mA cm -2 Stability curve under current density. As shown in the figure, the charcoal-based nanocatalyst -2 The catalyst can operate stably for 146 h at the current density with the required voltage increasing by only 3.6%, indicating that the embedded structure of high entropy alloy nanoparticles helps to enhance the interfacial stability of the catalyst.
[0119] The degradation experimental process of rhodamine B (RhB) was as follows: 150 mL of RhB aqueous solution (concentration of 25 mg / L) was prepared, 300 mg of charcoal-based nanocatalyst and 75 μL of 0.5 mM potassium persulfate (PMS) were added to trigger the degradation of RhB, and then 2.0 mL of the solution was extracted at designed time intervals, filtered with a polyvinylidene fluoride needle filter (0.45 μm), and the residual concentration of RhB was immediately measured with a UV spectrophotometer. Fig.15 The figure is a graph showing the degradation efficiency of Rhodamine B by efficient and stable charcoal-based nanocatalysts prepared by different heating processes, 1 is Example 4, 2 is Example 5, and 3 is Example 6. As can be seen from the figure, the charcoal-based nanocatalyst prepared by Example 4 exhibits a high catalytic activity, and can remove 99.5% of Rhodamine B within 10 minutes; as the reaction temperature increases, the number of carbon defect sites will decrease, and the cobalt metal salt will gradually evaporate, resulting in a decrease in the metal loading, which ultimately affects the degradation efficiency of the charcoal-based nanocatalyst.
[0120] After the catalytic reaction, the catalyst was rinsed with deionized water three times and then dried in an oven at 60 °C. The recovered catalyst was used for the cyclic degradation test under the same conditions, and the degradation test process was the same as Fig.15 The degradation time was 10 min each time. In each cycle experiment, the stability and recovery efficiency of the catalyst were evaluated based on the degradation of RhB. After the highly efficient and stable charcoal-based nanocatalyst prepared in Example 4 was used for 9 cycles, the catalyst surface was passivated in the 10th cycle experiment. Fig.16 This is a scanning electron microscope image of the longitudinal section of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 4 after passivation during the degradation of rhodamine B. As can be seen from the figure, after 10 cycles of use of the charcoal-based nanocatalyst, due to the adsorption of degradation intermediates, the surface presents a larger nanoflower structure, thereby hindering the reaction from continuing.
[0121] The regeneration method of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 4 is carried out according to the following steps:
[0122] ① The above-mentioned passivated efficient and stable charcoal-based nanocatalyst was fixed on the copper electrode of the Joule heating device, heated to 1600°C at a heating rate of 10000°C / s, and subjected to carbon thermal shock treatment for 2s at a temperature of 1600°C and an argon gas rate of 0.4L / min, and finally cooled to room temperature at a cooling rate of 2400°C / s;
[0123] ② Repeat step ① twice to complete the regeneration method and obtain the regenerated charcoal-based nanocatalyst.
[0124] Fig.17 This is a scanning electron microscope image of the longitudinal section of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 4 after passivation and regeneration by Joule heating. As can be seen from the image, after the charcoal-based nanocatalyst was regenerated at 1600°C, the cobalt nanoparticles regained their activity and showed a smooth spherical shape.
[0125] Fig.18 This is a transmission electron microscope image of the highly efficient and stable charcoal-based nanocatalyst prepared in Example 4 after passivation and regeneration by Joule heating treatment. As can be seen from the figure, after the charcoal-based nanocatalyst is regenerated at a high temperature of 1600°C, the reaction intermediates surrounding the cobalt catalyst have been converted into a graphite carbon layer structure, which not only promotes the recovery of active metal sites, but also enhances the local electron transfer of the catalyst.
[0126] Fig.19 The figure is a graph showing the degradation efficiency of Rhodamine B by the highly efficient and stable charcoal-based nanocatalyst prepared in Example 4 during 20 cycles; the charcoal-based nanocatalyst used in the 1st to 9th cycle experiments was prepared in Example 4; the degradation efficiency of the charcoal-based nanocatalyst used in the 10th cycle experiment was greatly reduced due to surface passivation; the charcoal-based nanocatalyst used in the 11th to 21st cycle experiments was a catalyst that was regenerated by Joule heating shock after passivation; and the cycle process and degradation process are the same as Fig.16 As can be seen from the figure, after multiple Joule heating treatments, the charcoal-based nanocatalyst achieved passivation-regeneration, and the degradation efficiency of Rhodamine B was higher than 90% in 20 cycles.
Claims
1. A method for preparing efficient and stable charcoal-based nanocatalyst based on Joule heating, characterized in that It is carried out in the following steps:
1. Preparation of transition metal salt solution: Adding a transition metal salt into a solvent and stirring to mix uniformly to obtain a transition metal salt solution; The concentration of the transition metal salt solution is 0.05 mol / L to 0.25 mol / L; 2. Carbonization activation: The wood is subjected to carbonization treatment and activation treatment in sequence to obtain activated charcoal; 3. Acid etching: The activated charcoal is immersed in an acid solution, etched for 10 minutes to 30 minutes at a temperature of 15° C. to 35° C., and then ultrasonically cleaned to obtain acid-treated charcoal; 4. Surface coating: ① Apply the transition metal salt solution to the surface of the acid-treated charcoal to fully wet the surface, and then vacuum-treat the wetted charcoal; ② Repeat step 4① 3 to 5 times to obtain charcoal after drop coating and impregnation, and heat the charcoal after drop coating and impregnation at a temperature of 50°C to 90°C for 8h to 24h to obtain charcoal loaded with a metal salt precursor; 5. Joule heating treatment: ① Fix the charcoal loaded with the metal salt precursor on the copper electrode of the Joule heating device, perform carbon thermal shock treatment for 0.5s to 2.5s at a temperature of 700℃ to 2400℃ and an argon gas rate of 0.2L / min to 0.8L / min, and finally cool to room temperature; ② Repeat step 5① 1 to 3 times to obtain a highly efficient and stable charcoal-based nanocatalyst.
2. The method for preparing an efficient and stable charcoal-based nanocatalyst based on Joule heating according to claim 1, characterized in that The transition metal salt described in step one is one of iron salt, cobalt salt, nickel salt, chromium salt and manganese salt or a combination of several thereof; the solvent described in step one is distilled water or anhydrous ethanol; the stirring and mixing described in step one is specifically stirring for 12h to 36h at a rotation speed of 300rpm to 600rpm.
3. The method for preparing an efficient and stable charcoal-based nanocatalyst based on Joule heating according to claim 2, characterized in that The iron salt is iron nitrate, iron chloride or iron acetate; the cobalt salt is cobalt nitrate, cobalt chloride or cobalt acetate; the nickel salt is nickel nitrate, nickel chloride or nickel acetate; the chromium salt is chromium nitrate, chromium chloride or chromium acetate; the manganese salt is manganese nitrate, manganese chloride or manganese acetate.
4. The method for preparing an efficient and stable charcoal-based nanocatalyst based on Joule heating according to claim 1, characterized in that The wood described in step 2 is pretreated wood, and the pretreatment is specifically carried out according to the following steps: soaking the wood in distilled water or ethanol solution, ultrasonically cleaning it for 1h to 3h at a power of 100W to 300W, and then vacuum drying it for 1h to 24h at a temperature of 40°C to 80°C to obtain the pretreated wood.
5. The method for preparing an efficient and stable charcoal-based nanocatalyst based on Joule heating according to claim 1, characterized in that The thickness of the wood in step 2 is 0.5 mm to 2.5 mm; the wood in step 2 is coniferous wood or broad-leaved wood, and the cutting method is transverse cutting or tangential cutting.
6. The method for preparing an efficient and stable charcoal-based nanocatalyst based on Joule heating according to claim 1, characterized in that In step 2, the wood is sequentially carbonized and activated, specifically according to the following steps: the wood is carbonized for 4 h to 8 h at a temperature of 800° C. to 1200° C. and a nitrogen flow rate of 0.2 L / min to 0.6 L / min, and after cooling to room temperature, the carbonized wood is obtained, and then the carbonized wood is activated for 2 h to 10 h at a temperature of 660° C. to 860° C. and a carbon dioxide flow rate of 0.05 L / min to 0.2 L / min, and after cooling to room temperature, the activated charcoal is obtained.
7. The method for preparing an efficient and stable charcoal-based nanocatalyst based on Joule heating according to claim 1, characterized in that The concentration of the acid solution described in step three is 5wt% to 25wt%; the acid solution described in step three is a nitric acid solution or a hydrochloric acid solution; the ultrasonic cleaning described in step three is specifically carried out according to the following steps: using distilled water or anhydrous ethanol as a washing liquid, ultrasonic cleaning is performed at a power of 200W to 500W until the pH of the solution is neutral.
8. The method for preparing an efficient and stable charcoal-based nanocatalyst based on Joule heating according to claim 1, characterized in that In step 4①, the drop coating volume is 2mL / cm 2 ~5mL / cm 2 , drop the transition metal salt solution onto the surface of the acid-treated charcoal to fully wet the surface, and then vacuum-treat the wetted charcoal for 24h to 72h in a vacuum environment at a temperature of 15℃ to 25℃ and a vacuum degree of 10Pa to 10kPa.
9. The method for preparing an efficient and stable charcoal-based nanocatalyst based on Joule heating according to claim 1, characterized in that In step 5①, the charcoal loaded with the metal salt precursor is fixed on the copper electrode of the Joule heating device, and the temperature is increased to 700℃~2400℃ at a heating rate of 8000℃ / s~12000℃ / s, and carbon thermal shock treatment is performed for 0.5s~2.5s at a temperature of 700℃~2400℃ and an argon gas rate of 0.2L / min~0.8L / min, and finally cooled to room temperature at a cooling rate of 2000℃ / s~2500℃ / s.
10. The method for regenerating the highly efficient and stable charcoal-based nanocatalyst prepared as claimed in claim 1, characterized in that It is carried out in the following steps: ① The passivated efficient and stable charcoal-based nanocatalyst is fixed on the copper electrode of the Joule heating device, and the temperature is increased to 700°C to 2400°C at a heating rate of 8000°C / s to 12000°C / s, and carbon thermal shock treatment is performed for 0.5s to 2.5s at a temperature of 700°C to 2400°C and an argon gas rate of 0.2L / min to 0.8L / min, and finally cooled to room temperature at a cooling rate of 2000°C / s to 2500°C / s; ② Repeat step ① 1 to 3 times to complete the regeneration method.
Citation Information
Patent Citations
Palladium nanoparticle / three-dimensional activated carbon composite catalyst as well as preparation method and application thereof
CN113318732A
Method for rapidly synthesizing platinum nano-particles with large number of dislocations
CN113967741A
Preparation method and application of electrocatalyst based on micro-connection interface thermal mismatch induced tensile strain
CN117488356A
Method for preparing one-dimensional nano carbide through rapid catalysis
CN117735552A
High-entropy alloy composite material and Joule thermal preparation method and application thereof
CN118186463A